The polymorphism G4C14-to-A4T14 in p73 gene may affect the susceptibility to male infertility with severe spermatogenesis impairment in Chinese population. (September 2016) - Xie, Ting; Yu, Cheng-He; Zheng, Ye; A, Zhou-Cun
Abstract: Objective: The aim of this study was to explore the association between the polymorphism G4C14-to-A4T14 in the p73 gene and male infertility with severe spermatogenesis impairment in Chinese population. Study design: Three hundreds and one infertile patients with severe spermatogenesis impairment (including azoospermia and severe oligospermia) and 252 fertile men were recruited in this study. The polymorphism G4C14-to-A4T14 in the p73 gene was genotyped using polymerase chain reaction and restriction fragment length polymorphism assay. The differences in allelic and genotypic frequencies between patients and controls were evaluated by chi-square test. Results: The frequency of allele AT (28.9% vs. 22.4%, P = 0.017, OR = 1.41, 95% CI = 1.07–1.85) in patients with severe spermatogenesis impairment was significantly higher than that in controls, whereas the genotype GC/GC was significantly decreased in patients compared with controls (48.5% vs. 59.1%, P = 0.048, OR = 0.65, 95% CI = 0.46–0.91). Conculusion: The findings of this study suggested that the polymorphism G4C14-to-A4T14 in p73 gene might be associated with severe spermatogenesis impairment and could affect the susceptibility to male infertility with severe spermatogenesis impairment in Chinese population.